Diagnóstico de atendimento ao código de segurança contra incêndio e pânico – CSCIP em igrejas evangélicas de grande porte em Curitiba - Proença, Rodrigo de Castro (2015)
This work aims to present a diagnosis of attention to security issues in churches with more than eighteen hundred members in Curitiba, specifically regarding emergency response. The analysis involves the application of an audit supported by a checklist developed based on CSCIP and applied to the sample selected institutions. After analyzing the evidence obtained was prepared nonconformities related service every CSCIP requirement applicable to the type of building. Thus, it was concluded that the sample of selected churches do not observe the law and does not adopt the procedures defined in CSCIP to ensure the safety of its members and property